Energy benchmarks. (TM (Chartered Institution of Building Services Engineers), 2008)
This publication offers a comprehensive outline of building energy benchmarks; what they are, how they were developed and how to use them. As well as the benchmarks themselves, it provides details of separable energy uses and includes weather and occupancy adjustments. If you want to understand the Display Energy Certificate (DEC) process better and see how ratings compare with energy benchmarks, this publication is for you. --